Identification of a novel regulatory protein (CsrD) that targets the global regulatory RNAs CsrB and CsrC for degradation by RNase E - Suzuki, Kazushi (Cold Spring Harbor Laboratory Press, 2006)
In Escherichia coli, the global regulatory protein CsrA (carbon store regulator A) binds to leader segments of target mRNAs, affecting their translation and stability. CsrA activity is regulated by two noncoding RNAs, CsrB and CsrC, which act by sequestering multiple CsrA dimers. Here, we describe a protein (CsrD) that controls the degradation of CsrB/C RNAs. The dramatic stabilization of CsrB/C RNAs in a csrD mutant altered the expression of CsrA-controlled genes in a manner predicted from the previously described Csr regulatory circuitry. A deficiency in RNase E, the primary endonuclease involved in mRNA decay, also stabilized CsrB/C, although the half-lives of other RNAs that are substrates for RNase E (rpsO, rpsT, and RyhB) were unaffected by csrD. Analysis of the decay of CsrB RNA, both in vitro and in vivo, suggested that CsrD is not a ribonuclease. Interestingly, the CsrD protein contains GGDEF and EAL domains, yet unlike typical proteins in this large superfamily, its activity in the regulation of CsrB/C decay does not involve cyclic di-GMP metabolism. The two predicted membrane-spanning regions are dispensable for CsrD activity, while HAMP-like, GGDEF, and EAL domains are required. Thus, these studies demonstrate a novel process for the selective targeting of RNA molecules for degradation by RNase E and a novel function for a GGDEF–EAL protein.